Underground” Studi Deskriptif Komunitas Underground Di Kota Padang - Tri Fajri; Marzam Marzam (SENDRATASIK UNP, 2020)
This research aims to find and describe the activities of underground community in Padang. Type of this research was qualitative. The main instrument in this study was the researcher. The additional instruments used stationery, recording device and camera. Techniques of data collection were done by taking observation, interviews, literature study and documentation. The steps in analyzing data were carried out by collecting, describing and making conclusion of data. The results show that the number of negative responses from ordinary society to the underground community. Underground is a movement which is not tied to a corporation that is binding. The underground movement is counterculture. Judging from the way they are dressed and the accessories used, unclear and noisy music, underground music is considered as satanic, unhealthy lifestyles such as drugs and drinking. The underground communities respond to the negativeresponse by being apathetic. Yet, they can only show to the general public in particular with activities that are positive for the outside society, for example, such as food not bombs, mayday, free market and reading booths.